2014
DOI: 10.1185/03007995.2014.901942
|View full text |Cite
|
Sign up to set email alerts
|

Assessing age and gender in studies of breakthrough pain medications

Abstract: There is a need for more information regarding the use of opioids for BTP according to age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The studies on the treatment of pain in older patients are sparse. Mercadante and Giarratano in their systematic review of differences between adults and older persons and between male and female patients in randomized clinical trials on pain identified only three studies that focused on the population of advanced age (Mercadante and Giarratano, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the treatment of pain in older patients are sparse. Mercadante and Giarratano in their systematic review of differences between adults and older persons and between male and female patients in randomized clinical trials on pain identified only three studies that focused on the population of advanced age (Mercadante and Giarratano, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of BTcP in patients with cancer still remains a primary challenge in the integral management of cancer patients, particularly in the elderly [12, 32]. However, it is generally agreed that there is a need for more information regarding the use of opioids for BTcP in older individuals [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, age subgroup analysis of efficacy or adverse effects of BTP medications has been rarely reported in the literature and deserve further examination [ 5 , 10 ]. To date, no studies exist examining the effect of age on SFT dosing on pain symptoms and QoL.…”
Section: Introductionmentioning
confidence: 99%